2004
DOI: 10.1590/s0100-84042004000100010
|View full text |Cite
|
Sign up to set email alerts
|

In vitro somatic embryogenesis and adventitious root initiation have a common origin in eggplant (Solanum melongena L.)

Abstract: -(In vitro somatic embryogenesis and adventitious root initiation have a common origin in eggplant (Solanum melongena L.)). Somatic embryogenesis was induced from cotyledon explants of eggplant cultured on MS medium supplemented with 54 µM NAA. Anatomical analysis of somatic embryo initiation and development was performed during the first four weeks. Proembryo formation was observed after the second day of culture, directly from perivascular cells or via pro-embryogenic masses derived from indeterminate merist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…You et al (2006) verified a high correlation between callose deposition on the cell wall of Eleutherococcus senticosus and beginning of proembryos development. The apparent thickening of the cell wall around proembryos was also verified in other events of somatic embryogenesis induction, such as in calli of Phoenix dactylifera (Sané et al 2006) and Solanum melongeana (Tarré et al 2004). The fact that only a few number of the embryos of unicellular origin proceeded to advanced phases can be explained by competition between them or by the lack of other components needed for their regeneration and maturation on the culture medium.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…You et al (2006) verified a high correlation between callose deposition on the cell wall of Eleutherococcus senticosus and beginning of proembryos development. The apparent thickening of the cell wall around proembryos was also verified in other events of somatic embryogenesis induction, such as in calli of Phoenix dactylifera (Sané et al 2006) and Solanum melongeana (Tarré et al 2004). The fact that only a few number of the embryos of unicellular origin proceeded to advanced phases can be explained by competition between them or by the lack of other components needed for their regeneration and maturation on the culture medium.…”
Section: Discussionmentioning
confidence: 54%
“…Buffard-Morel et al (1992) verified that the same auxin could induce root formation and somatic embryos in Cocos nucifera. Tarré et al (2004) verified that the same type of cell from Solanum melongeana vascular tissue could lead to the formation of somatic embryos or root primordia.…”
Section: Discussionmentioning
confidence: 84%
“…In S. melongena, regeneration from the cotyledonary explants at different developmental stages ranging from one week old to 30 days old have been reported (Alicchio et al, 1982;Fobert and Webb, 1988;Rao, 1992;Saito and Nishimura, 1994;Momiyama et al, 1995;Sharma and Rajam, 1995;Hitomi et al, 1998;Magioli et al, 1998;Scoccianti et al, 2000;Tarre et al, 2004;Rahaman et al, 2006). Rama Swami et al (2005) reported in vitro response of cotyledons from three week old seedlings of S. surattense.…”
Section: Discussionmentioning
confidence: 99%
“…In peanut, embryos can be formed from meristematic cells of calli derived from cotyledons, from parenchymatic cells of young leaves or from meristematic and submeristematic cells of apical meristems (Sagare et al 1995). In eggplant, somatic embryos induced by NAA are formed from perivascular parenchymatic cells originating indeterminate meristematic masses, which can either give rise to adventitious roots or pro-embryogenic masses (Tarré et al 2004).…”
Section: Tissue Culturementioning
confidence: 99%